201 Characteristics of Patients with Erectile Complaints Referred to a Center of Excellence – Defining Complex Erectile Dysfunction. Issue 1 (1st April 2022) - Haehn, D; Baird, B; Ball, C; Broderick, G
ABSTRACT: Introduction: The prevalence of erectile complaints in the US is estimated to be more than 50%. Most of the time ED complaints are evaluated and treated in the primary care setting. However, when first line measures are not efficient, patients are referred to general Urologists or to a specialized center. Objective: The primary aim of this study is to describe the characteristics of patients referred to a tertiary center for evaluation of erectile complaints not responding to traditional first line therapies and, or patients with an associated complaint of penile deformity (rule out Peyronie's Disease/PD). Methods: We retrospectively analyzed a cohort of patients between 2005 and 2019, detailing primary complaints, sexual histories, self-assessment scores, medical history and results of in office intracavernous injection followed by Color Doppler Duplex Ultrasound (CDDU). CDDU findings were recorded following injection of low dose alprostadil (10-20 mcg) and again after a period of privacy and visual sexual stimulation. CDDU findings including peak systolic velocities (PSV), and resistive indices (RIs) were recorded. Arterial insufficiency (AI) was defined as either a post-stimulation PSV < 25 (severe) or a PSV 25-34.9 with RI ≥ 0.9 (moderate). Cavernous venous occlusion disease (CVOD) was defined as post-stimulation PSV ≥35 with RI < 0.9. Vascular normal was defined as post-stim PSV ≥ 35 with RI ≥ 0.9. Results: A total of 1490 patients with a median age of 60 (range, 18 – 88), median BMI of 28.4 (range, 15.9 – 56.8) and median Sexual Health Inventory for Men (SHIM) score of 10 (range, 0-25). In our cohort, 257/1489 (17.3%) patients had heart disease, 656/1489 (44.1%) patients had hypertension, 520/1489 (34.9%) patients had diabetes, and 203/1488 (13.6%) patients had a past medical history of hypertriglyceridemia. Smoking history was present in 853/1478 (57.7%) of patients and complaint of PDE-5 failure was made by 945/1201 (78.7%) patients who reported using it. 900 patients (60.4%) had a complaint of penile deformities and ED, 461 (30.9%) had a complaint of ED only, and 129 (8.7%) had a complaint of PD only. Prostate surgery history was noted in 316 men: radical retropubic prostatectomy 108, robotic assisted prostatectomy 134 and endoscopic resection or enucleation 74. Following CDDU we confirmed 767 (51.5%) patients with both ED and PD, 351 (23.6%) with ED only, and 310 (20.8%) PD only. We found 62 men (4.2%) had normal vascular erectile response to low dosage PGE1 (diagnosed as psychogenic ED vs. post-prostatectomy neurogenic ED). Among the 351 patients with ED only on Doppler, 132 (37.6%) had AI, 124 (35.3%) had CVOD, and 95 (27.1%) had a mixed vascular diagnosis. Among patients with vascular ED on diagnoses by CDDU, 73/351 (20.8%) had heart disease, 192/349 (55.0%) had smoking history, 273/311 (87.8%) complained of PDE5-inhibitor failure, 130/351 (37.0%) had diabetes, and median SHIM score was 7 (range 1-25). Conclusions: This summary describes the characteristics in 1490 men who presented for evaluation of erectile complaints and or complaints of penile deformity to a tertiary care center. Patients referred to Urologists have complex ED, defined as refractory to PDE5-Inhibitors, associated with penile deformities, and multiple medical / surgical risk factors. Disclosure: No